Trabalho docente e políticas educacionais : um estudo sobre o controle do trabalho docente na rede estadual de ensino de Minas Gerais em Uberlândia a partir de 2003 - Martins, Elizeth Rezende (2016)
This study it is an investigative work of Master under the Graduate Program in Education of the Federal University of Uberlândia linked to the Working survey line, society and education. The goalis to analyze the impacts and the new settings that teaching as taken on the state system of Minas Gerais in Uberlândia-after the implementation of educational policies guided by the managerial rationality by Governor Aécio Neves, from the year2003. The central element Research is the Individual Performance Assessment (ADI) as regulatory policy coming from the institutional apparatus of the State Reform - Call Management Shock. The aim is to verify the changes in teaching from this evaluation process embodied in assessment policies to control the teaching work. It brings the context of the restructuring that took place in recent years in the educational sphere and in teaching, given the capital\'s globalization scenario. The study supports in reading and analysis of documents such as the Constitution of 1988, the Law of Guidelines and Bases of Education No. 9.394 / 96 Pedagogical Policy Project Institutional, Career Plan of the State Network of Mining Education, Resolutions, Guidelines bodies responsible for deciding on educational policies in Brazil and documents provided by the Sind-UTE - representative of the teaching category in Uberlândia. It is a qualitative research that permeates the literature review and the classic discussing the issue with a view to recovery and analysis of the production on the teaching. The hypothesis that guides the study is that the resulting changes in education reform over the last few years have led to erosion and intensification of teaching work generating professional illness. From the government\'s demands Mineiro has been increased functions and tight control over the teaching, with interference in the pedagogical and working conditions. The results preliminary data indicate that teachers love what they do and intend to do a good job, but by the need to teach at more than one school, the lack of time to prepare lessons, the lack of conditions to perform quality its activities; in addition to the work overload and lack of salary incentives, there is a great motivation to teaching.